The Role of Defense Diplomacy in Strengthening Indonesia–France Relations: A Case Study of Defense Equipment Procurement - Saleo, Aloycius Chandra Londong Somalinggi; Perwita, Anak Agung Banyu; Hendarwoto, Yermia (Darul Yasin Al Sys, 2025)
This study investigates the role of defense diplomacy in enhancing bilateral relations between Indonesia and France, with particular emphasis on defense equipment procurement as a strategic instrument. Grounded in neorealism, cooperative security theory, and the concept of defense diplomacy, the research explores how Indonesia’s acquisition of French military platforms, including Rafale fighter jets and Scorpène-class submarines, extends beyond arms transactions to encompass trust-building, capability development, and regional power balancing. Employing a qualitative case study approach supported by policy analysis, defense agreements, and secondary literature, the study demonstrates that defense procurement has strengthened bilateral strategic alignment while advancing Indonesia’s military modernization agenda. The findings indicate that defense diplomacy can serve as an effective bridge between hard power imperatives and soft power engagement, particularly within the increasingly contested Indo-Pacific context. This research contributes to scholarly debates on middle power diplomacy and underscores the multidimensional value of defense cooperation in achieving foreign policy and security objectives.